Immortality : the other side of death - Habermas, Gary R.; Moreland, James Porter, 1948- (Nashville, TN : T. Nelson, 1992)
"The evidence for life after death. What near-death experiences tell us. The case for the existence of heaven and hell"--Cover.
Beyond life's "certainties" -- The Evidence for Immortality : Some reasons to believe -- Body and soul -- Dualism and eternal life -- The Resurrection of Jesus -- Near-death experiences -- NDEs : questions and objections -- The Nature of Immortality : Life in between : the state between death and eternity -- Reincarnation, is it true? -- The Afterlife's ultimate model -- Heaven : the great adventure -- Hell : the horrible choice -- The Implications of Imortality -- Becoming Heavenly minded -- Overcoming the fear of death -- Dealing with abortion, infanticide, and euthanasia -- Eternity in the balance.
Includes bibliographical references (p. 226-275)
Keywords: Future life -- Christianity